JAK Inhibition: The Most Promising Agents in the IBD Pipeline? - Fernández-Clotet, Agnès; Castro-Poceiro, Jesús; Panés, Julián (Current Pharmaceutical Design, 2019)
Under current therapeutic algorithms, half of the patients with moderate-severe ulcerative colitis or Crohn’s disease fail in achieving a sustained remission. New drugs with different mechanisms of action are needed. After two decades of new drug avenues in inflammatory bowel disease dominated by the development of monoclonal antibodies, in recent years we are witnessing promising developments of small molecules for these conditions. Their intrinsic characteristics make them attractive compared to the monoclonal antibodies based on their oral administration, short plasma half-life, lack of immunogenicity and predictable pharmacokinetics. Among them, Janus kinase (JAK) inhibitors are a promising new class that have demonstrated efficacy with a favorable safety profile in clinical trials. Tofacitinib has been the first JAK inhibitor approved for the treatment of ulcerative colitis. This review discusses the molecular aspects of the JAK-STAT pathway, its role in the pathogenesis of inflammatory bowel disease, and the rational use of JAK inhibitors in these conditions. The different compounds with JAK inhibitory activity tested are reviewed and we provide an overview of recent evidence from clinical trials. Finally, we consider the positioning of these drugs in the treatment of inflammatory bowel diseases.
Keywords: Crohn' s disease